(untitled) (American Journal of Innovation in Science and Engineering, 2023)
The rotor of a palm nut cracker must be designed in such a way as to overcome friction, wears, the collision of nuts, etc. during nut cracking. Thus, there is a need to find the efficiency (rotor operating factor) Kf of the rotor and then used it to obtain the actual operating rotor speed in revolution per minute (rpm) for effective operation. In this study, masses of palm nuts (ḿ), its exit velocity from the rotor disc (v), rotor radius (r), axial dimensions, and energy generated due to friction, sound, heat, etc. (Ef), palm nut translational kinetic the energy (KEtrans), energy released per unit nut (Q) and inverse of theoretical rotor speed (Nt-1) were used based on some existing models. Plots of r against Nt-1 to determine the slope and thereafter evaluate Kf were carried out. The effect of ḿ on Kf was assessed using Analysis of Variance at 5% level probability. The results showed that the mean Kf was 0.76 and was not affected by varying ḿ since the calculated probability was 0.002 and r-squared was 0.324. The actual rotor speed could be found as the product of Kf and Nt.